Concevoir un Environnement Numérique pour la pédagogie universitaire : le programme NéopassSup - Sylvia Heurtebize; Luc Ria (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article reports on the design stages of a Digital Environment to Help Understanding and Transforming Situations (ENACTS) designed to support the professional pedagogical development of higher education teachers. It presents the environment by contextualizing its creation and updating the theoretical and methodological presuppositions underlying its design guided by an activity analysis research program. It identifies the components of a media and pedagogical script allowing the transition from video resources to an environment potentially capable of provoking and supporting the pedagogical professional development of higher education teachers. Finally, it discusses the conditions of professional development from it and questions its reproducibility.